Potential utilization of the weapon system tank boat in strengthening the defense of Indonesia as a maritime country (Defense and Security Studies, 2022)
Indonesia is the largest maritime country in the world with 80 percent of its territory in the form of oceans. This makes it difficult to supervise the security and sovereignty of the Republic of Indonesia, especially in the maritime sector. Therefore, it is necessary to design a fast catamaran concept that is good and responsive as a tool for war and security in Indonesia's maritime territory. This study aims to design the concept of a Tank Boat type ship and a weapon system based on domestic weapons technology. The method used is the House of Quality data analysis technique which is the first stage of implementing Quality Function Deployment (QFD) in classifying user needs based on the level of importance so that a priority scale is obtained. From the results of the analysis using the Quality Function Deployment (QFD) method, the level of user needs for ships and weapon systems on Tank Boats based on weapons technology is obtained by determining the Benchmark Performance (BP) value for the highest to lowest design characteristics. In this case, there are several main points for the desired user needs in the operational requirements and weapon systems for the Tank Boat object, including Tank Boat has lightweight, The weapons used have high precision, Weapons must be free from ITAR (International Traffic Regulations), The flexibility of weapons to be integrated with the vehicle, The main target is a vital target or VVIP, and Security. The results of the study indicate that there is a need for a weapon system on the Tank Boat to support the defense of the Maritime State. This research is expected to be used as a starting point for further research related to ships and weapon systems that can be used on Tank Boat rides.